Chemical profiling, antimicrobial and insecticidal evaluations of Polygonum hydropiper L. Issue 1 (December 2016) - Ayaz, Muhammad; Junaid, Muhammad; Ullah, Farhat; Sadiq, Abdul; Ovais, Muhammad; Ahmad, Waqar; ahmad, Sajjad; Zeb, Anwar
Abstract Background The emergence of multidrug resistant (MDR) pathogens is of great concern to the global health community. Our ability to effectively treat diseases is based on the discovery of potent drugs for the treatment of these challenging diseases. Traditional medicines are one of the major sources for the discovery of safe, effective and economical drug candidates. In order to validate its antibacterial, antifungal and insecticidal potentials with respect to traditional uses, we have screened for the first timePolygonum hydropiper against pathogenic bacterial, fungal strains and a variety of insects. Methods Polygonum hydropiper samples including crude extract (Ph.Cr), subsequent fractions;n -hexane (Ph.Hex), chloroform (Ph.Chf), ethyl acetate (Ph.EtAc), n -Butanol (Ph.Bt), aqueous (Ph.Aq) and crude saponins (Ph.Sp) were tested against pathogenic bacterial and fungal strains. Insecticidal activities were performed againstTribolium castaneum andRhyzopertha dominica andMonomorium pharaonis. Ph.Cr was analyzed by gas chromatography–mass spectrometry (GC-MS) for preliminary identification of chemical constituents. Results In disc diffusion assay, Ph.Chf, Ph.Hex, Ph.EtAc and Ph.Sp exhibited highest activity againstEnterococcus faecalis. MICs of Ph.Chf againstEnterococcus faecalis, Klebsiella pneumoniae, Escherichia coli, P. mirabilis, Staphylococcus aureus, Salmonella typhi andPseudomonas aeruginosa were 32.00, 13.33, 10.66, 5.33, 64.00, 8.66 and 10.66 μg/ml respectively. MFC's of Ph.Chf againstAspergillus fumigatus, Aspergillus flavus, Aspergillus niger andFusarium oxysporum were 16.66, 23.33, 125.00 and 46.66 μg/ml respectively. Ph.EtAc, Ph.Sp, Ph.Chf and Ph.Bt were most active fractions againstT. castaneum andR. dominica . Ph.Sp being most active againstA. punctatum exhibited LC50 of < 0.01 mg/ml. In GC-MS analysis of Ph.Cr, 124 compounds were identified among which several bioactive antibacterial, antifungal and insecticidal compounds were found. Conclusions P. hydropiper samples exhibited broad spectrum of activity against bacterial and fungal strains. Our results support previously reported insecticidal properties of saponins and may provide scientific justification for the ethno-medicinal uses of the plant.